The French of Outremer : communities and communications in the crusading Mediterranean - Morreale, Laura K.; Paul, Nicholas, 1977- (Fordham series in medieval studies., 2018)
A collection of essays devoted to the culture of the Francophone European crusading states of the eastern Mediterranean. Contributors, including historians of the crusades, Old French literature, and medieval art, each address different themes and questions related to life, literature, and language in the Frankish Levant.